A Comprehensive Review on The General Concepts and Applications of Artificial Intelligence - Ishwarya M.V,; Jayashree Ananth,; M.Suresh Anand, (AG Volumes, 2022)
An artificial intelligence (AI) is a computer programme that mimics human behaviour or thinking and may be taught to tackle certain issues. Deep Learning as well as Machine Learning are used to create artificial intelligence (AI). To be able to make intelligent judgments, AI models must be educated utilising a lot of data. Artificial Intelligence (AI) is becoming more and more popular as a tool and as a concept. Computer programmes with artificial intelligence (AI) may reason and adapt based on their interactions with the world around them. The use of artificial intelligence (AI) in business has grown dramatically in recent years which has found its way into practically every industry. This paper presents some of the fundamental concepts in AI and also reviews the most popular real-world AI applications.